Pelatihan Penyusunan Laporan Keuangan Koperasi Kenten Mandiri Jaya - Hasudungan Rajagukguk, Ronald (Jurnal Pengabdian Masyarakat Inovasi, 2024)
Cooperatives are the backbone of the people's economy and play a strategic role in improving community welfare, yet the primary challenge often faced is the low quality of financial accountability. Kenten Mandiri Jaya Cooperative, located in Banyuasin and operating in the palm oil plantation sector, faces obstacles in preparing financial statements that comply with applicable accounting standards. The main issues include limited human resource capacity in mastering the accounting cycle and the use of information technology. The objective of this community service activity is to enhance the competence and independence of cooperative managers in preparing accurate, transparent, and accountable financial reports based on SAK ETAP and the Regulation of the Minister of Cooperatives and SMEs No. 12 of 2015. The implementation methods used in this activity include the lecture method for theoretical delivery, the interactive Q&A method for discussing field cases, and the direct hands-on training method using Microsoft Excel with real cooperative data. This activity involved cooperative managers and a team of tax experts to provide a holistic understanding of financial reporting and fiscal obligations. The results of the service show a significant increase in the participants' knowledge and technical skills. The managers are now capable of performing the journalizing process, filling out ledgers, and generating balance sheets and income statements (PHU) independently. In conclusion, through this training, Kenten Mandiri Jaya Cooperative has successfully implemented a more standardized financial reporting system, which is expected to increase member trust and strengthen professional organizational governance.